ETHNOBOTANY: VALUING LOCAL KNOWLEDGE ABOUT MEDICINAL PLANTS BY TRADITIONAL COMMUNITIES (Interdisciplinary Studies Journal, 2024)
This systematic review looked at aspects of ethnobotany experienced by Amazonian communities. Articles were examined from the databases Periódicos Capes, Scopus Scielo and Science Direct, using search terms such as Amazon, ethnobotany, ethnobotany and traditional knowledge, ethnoknowledge, ethnoscience, ethnoconservation, ethnobiodiversity, agroecology and medicinal plants, combined with the Boolean operator "AND", ethnobotany AND Amazon; ethnobotany AND community; ethnobotany AND ethnoconservation; ethnobotany AND ethnoscience; ethnobotany AND medicinal plants. The exclusion criteria were based on the date the study was carried out and published, the biome, the population studied, the methodology and the object of the study differing from that proposed. The results were structured into three main categories: Ethnobotany, Traditional Communities and Medicinal Plants. The Ethnobotany category discusses the relationship between human beings and plants, highlighting how they are used as a resource. Traditional communities, covered in the second category, emphasize their cultural identity and the use of natural resources for their subsistence. The third category discusses the use of medicinal plants by the communities. It was concluded that ethnobotany focuses on the study of the recognition of traditional communities, their culture and way of life, as well as contributing to the conservation of natural resources by these communities.
Keywords: Ethnoknowledge; Amazonia; Popular Knowledge